First report of the moss Rhynchostegiella divaricatifolia (Renauld & Cardot) Broth. from Western Himalayan region of India - Saxena, D. K.; Kumar, S.; Saxena, S. (Phytotaxa, 2014)
Study of the bryoflora of the Western Himalayas revealed for the first time the presence of the moss taxon Rhynchostegiella divaricatifolia from the Kumaon region. Earlier this moss was known from the eastern part of the country, i.e. Darjeeling (Sikkim), and was considered unique to that region. The present study describes the extended range of distribution from the Eastern Himalayan to the Kumaon hills of India in an area of 21,035 km(2). Rhynchostegiella divaricatifolia is characterised by a twisted half turn leaf apex, leaf cells showing irregular primordial utricle, linear, irregularly rhomboid. The moss plants are soft, large, glossy, and yellow-green in lax tufts.